Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 78. Beitrag. Hymenoptera: Apidae IV (Bombinae). - Tkalců, Bořivoj (Contributions to Entomology = Beiträge zur Entomologie, 1969)
The collection of bees made by the expedition to Albania by Deutsches Entomologisches Institut in 1961 contains 19 species of the subfamily Bombinae. Four oi them, Bombus lucorum (Linnaeus), Megabombus pomorum (Panzer), Megabombus subterraneus latreillellus (Kirby) and Psithyrus sylvestris Lepeletier, proved to be new in Albania. Including previous publications we find that of the 39 species recorded from the Balkan peninsula, 24 species are now known from Albania. The present table lists some other species whose occurrence in that region is possible or even highly probable. For many taxa the type material or the established lectotypes are discussed, and for some species taxonomie notes including the newly ascertained synonymy are added. Nomenclatural Acts dumoucheli Radoszkowski, 1884 (Bombus), syn. n. of Megabombus (Rhodobombus) armeniacus (Radoszkowski, 1877) lefebvrei Lepeletier, 1836 (Bombus), syn. n. of Megabombus (Rhodobombus) pomorum (Panzer, 1805) rufescens Lepeletier, 1836 (Bombus), syn. n. of Megabombus (Rhodobombus) pomorum (Panzer, 1805) ponticus Grütte, 1940 (Psithyrus (Allopsithyrus)), syn. n. of Psithyrus (Allopsithyrus) maxillosus (Klug, 1817) anatolicus Grütte, 1940 (Psithyrus (Allopsithyrus) barbutellus), syn. n. of Psithyrus (Allopsithyrus) maxillosus (Klug, 1817)